Magnetic order in the purely organic quasi-one-dimensional ferromagnet 2-benzimidazolyl nitronyl nitroxide - Sugano, T; Blundell, S; Lancaster, T; Pratt, F; Mori, H (2010)
We show that the quasi-one-dimensional organic ferromagnet 2-benzimidazolyl nitronyl nitroxide (2-BIMNN) undergoes a phase transition to long-range magnetic order below TC =1.0 (1) K. The intrachain exchange interactions are J/kB =22 K and so the low-temperature ordering demonstrates the weakness of the interchain interactions. Our electron-spin-resonance measurements provide further evidence for the one-dimensional character of the magnetic fluctuations in 2-BIMNN and, using muon-spin rotation, we are able to characterize the broad phase transition in the material. We discuss these results in the context of other spin- 1 2 quasi-one-dimensional Heisenberg ferromagnets and demonstrate that 2-BIMNN is the best realization of a one-dimensional Heisenberg ferromagnet among purely organic compounds yet discovered. © 2010 The American Physical Society.